Nutritional Interventions and Wound Healing Outcomes in Patients With Diabetic Foot Ulcers: A Systematic Review - Siti Kotijah; Nur Chayati; Shanti Wardaningsih; Fitri Arofiati (Media Publikasi Cendekia Indonesia, 2026)
Diabetic foot ulcers (DFU) are a severe complication of diabetes mellitus that contribute to delayed wound healing, increased amputation risk, and substantial healthcare burden. Beyond vascular and metabolic abnormalities, malnutrition plays a critical role in prolonging inflammation, impairing collagen synthesis, and delaying tissue regeneration. Although nutritional support is increasingly incorporated into DFU management, its clinical effectiveness remains variably reported. Therefore, this study aimed to evaluate the effects of nutritional interventions and the association between nutritional status and wound healing outcomes in patients with DFU. This systematic review was conducted in accordance with PRISMA 2020 guidelines. The methodological quality of included studies was assessed using the Joanna Briggs Institute (JBI) Critical Appraisal Tools. The review protocol was not registered in PROSPERO. Articles were retrieved from PubMed, Scopus, and ProQuest using the keywords “diabetic foot ulcer”, “nutritional intervention”, and “wound healing”. Inclusion criteria comprised original quantitative studies published in English between 2022 and 2026 involving adult DFU patients. Data were extracted using structured tables and synthesized narratively. Nine eligible studies demonstrated that nutritional interventions, including oral nutritional supplementation, micronutrient supplementation, dietary modification, and nutrition-related multidisciplinary approaches, were associated with greater wound size reduction, improved inflammatory biomarkers, and enhanced re-epithelialization. Observational evidence consistently showed that poor nutritional status was linked to higher ulcer severity and increased amputation risk. Nutritional optimization appears to be a clinically meaningful component of DFU management and may be beneficial when integrated into comprehensive care strategies.